1986
DOI: 10.1007/bf02213991
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of extra iron supply in veal calf fattening

Abstract: Extra iron (5 ppm) in a normal commercial milk replacer given from the end of the sixth week until the end of the sixteenth week of the fattening period influenced food conversion positively without a loss in meat quality. Even when the extra iron was given to the end of the fattening period there was no perceptible improvement of the haematological status of the calf, though liver iron concentration was increased. During all the experiments no stainable iron could be found in bone marrow smears. Iron and copp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…These studies suggest that Fe has a significant effect on the hematocrit only when the body is extremely deficient in Fe. The present experiment similarly showed that Fe (50 to 150 mg/kg) had no effect on hematocrit of yellow-feathered broiler chickens aged 1 to 63 days; additionally, there was no effect on Fe content of the kidney and liver, sensitive and reliable tissues reflecting Fe deposition [39,40]. Ma [5] found that Fe content in the kidney of AA broiler chickens aged 22 to 42 d was not significantly affected by dietary Fe level (40 to 140 mg/kg).…”
Section: Discussionsupporting
confidence: 64%
“…These studies suggest that Fe has a significant effect on the hematocrit only when the body is extremely deficient in Fe. The present experiment similarly showed that Fe (50 to 150 mg/kg) had no effect on hematocrit of yellow-feathered broiler chickens aged 1 to 63 days; additionally, there was no effect on Fe content of the kidney and liver, sensitive and reliable tissues reflecting Fe deposition [39,40]. Ma [5] found that Fe content in the kidney of AA broiler chickens aged 22 to 42 d was not significantly affected by dietary Fe level (40 to 140 mg/kg).…”
Section: Discussionsupporting
confidence: 64%
“…Hemoglobin values significantly (P < 0.0001) correlated with 45-min and 3-day Y values, in agreement with previous reports (Wensing et al,, 1986;Beauchemin et al, 1990;Agboola et al, 1988). Using hemoglobin as a predictive factor in the regression equation increased R2 to 0.59 and reduced RSE to 5.73 which constituted a notable but still insufficient improvement in predictive accuracy (3-day Y = 1.45 (45-min Y) -0.31 Hb + 25.48).…”
supporting
confidence: 92%
“…Wensing et al (1986) reported that iron supply management during the fattening period to control veal color is more reliant on blood hemoglobin concentration than on plasma iron concentration. Although blood hemoglobin concentration was numerically lower for catechins, wheat bran and CW than that of steers fed a basal diet (control), there was no correlation between blood hemoglobin or plasma iron concentration and total muscle iron concentration in the present study.…”
Section: Resultsmentioning
confidence: 99%